CLOVES syndrome: An unusual presentation of a rare entity - Pallavi Hegde; Vikrant Choubey; Bijaylaxmi Sahoo (Wolters Kluwer Medknow Publications, 2022)
CLOVES syndrome is a rare disorder that falls under the spectrum of clinically and etiologically heterogenous "vascular malformation with limb overgrowth syndromes." An 8-year-old male child presented with overgrowth of limbs, multiple vascular malformations, epidermal nevus, skeletal anomalies, and undescended testis, based on which a diagnosis of CLOVES syndrome was made. This publication serves to discuss the classical features of this rare syndrome and to report undescended testis, which is an unusual feature. Identifying this variable constellation of features is essential to differentiate the condition from other similar disorders for purposes of academics, research, and patient care.